Genetic analysis of downy mildew resistance in pearl millet - and R.K. SHEORAN, D.P. DESWAL, O.P. GOVILA (Indian Phytopathology, 2002)
Experiments were conducted to estimate gene effects and G (genetic) X E (environment) interactions for downy mildew disease (caused by Sclerospora graminicola) in pearl millet (Pennisetum glaucum). Six generations of 2 crosses, resistant X susceptible (’PPM1519’ X ’23B’) and susceptible X susceptible (’23B’ X PPMI 318’), were grown at 2 locations (Delhi and Villupuram, Tamil Nadu, India) during 1987-88, for disease severity recording. The least square method was applied. It was observed that G X Einteractions were present for downy mildew severity. In the inheritance of resistance to downy mildew both additive and non-additive gene effects were important. Epistatic interactions were present in low magnitude. The duplicate type of epistasis was observed except in the R X S cross at location E1. It is concluded that the utilization of G X E interactions for pathogen expression should be given due consideration in resistance breeding.